2021
DOI: 10.3390/min11040384
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mapping to Evaluate Post-Depositional Diagenesis among the Earliest Ceramics in the Teotihuacan Valley, Mexico

Abstract: Chemical and mineral sourcing techniques are commonly employed in archaeology to reconstruct patterns of ceramic exchange and raw material procurement practices for the past, but the effects of post-depositional diagenesis are still often ignored despite a number of key studies warning that the composition of ceramics from archaeological deposits often diverges greatly from their original composition at the time of production. This current study on diagenesis derives from a large chemical and petrographic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Gilstrap et al [10] explore the diverse ways in which calcium-containing minerals can be altered in ceramics, including case studies from terrestrial and marine environments using petrographic and elemental analysis. Stoner and Shaulis [11] examine alterations in low-fired ceramics from the Valley of Mexico using profile mapping by LA-ICP-MS, demonstrating substantial Ba enrichment in the outer margins of some of the ceramics they study, as well as the uptake of a number of metallic elements. Golitko et al [12] examine the composition of dense surface encrustations found on Bronze Age ceramics from eastern Hungary using a combination of mineralogical and chemical methods of characterization, identifying soil carbonates and phosphates as the likely source of surface concretions.…”
mentioning
confidence: 99%
“…Gilstrap et al [10] explore the diverse ways in which calcium-containing minerals can be altered in ceramics, including case studies from terrestrial and marine environments using petrographic and elemental analysis. Stoner and Shaulis [11] examine alterations in low-fired ceramics from the Valley of Mexico using profile mapping by LA-ICP-MS, demonstrating substantial Ba enrichment in the outer margins of some of the ceramics they study, as well as the uptake of a number of metallic elements. Golitko et al [12] examine the composition of dense surface encrustations found on Bronze Age ceramics from eastern Hungary using a combination of mineralogical and chemical methods of characterization, identifying soil carbonates and phosphates as the likely source of surface concretions.…”
mentioning
confidence: 99%